Critical Period of Tomato toAlternariasokuri (Ell. & G. Martin) Sor. infection and its determinant. Determination of critical period (susceptible period) of plant is one of the strategies in Integrated Pest Management (LPM), because it can reduce or minimize pesticide use. Study about the critical penendo of tomato was cam'ed out in the field of Bangbayang village, in the Cicwug district of Sukubumi. Tomato plant cultivar Zntan at dzremnt age (50, 60, 70 and 80 &ys after sowing [DAS - Sientje Mandang Sumaraw (Buletin Hama dan Penyakit Tumbuhan, 1999)
Critical Period of Tomato toAlternariasokuri (Ell. & G. Martin) Sor. infection and its determinant. Determination of critical period (susceptible period) of plant is one of the strategies in Integrated Pest Management (LPM), because it can reduce or minimize pesticide use. Study about the critical penendo of tomato was cam'ed out in the field of Bangbayang village, in the Cicwug district of Sukubumi. Tomato plant cultivar Zntan at dzremnt age (50, 60, 70 and 80 &ys after sowing [DAS] were inoculated with 15 ml of Id s p o l suspension of Alternaria solani per plant, that have been added with Agristick 2% and llveen 80 2%. Observation that was conducted include disease severity, the height of plant, dry weight of plant biomass and total Jiuit production. Leaves of diferent age (50, 60, 70, 80 DAS) at d@rent part of plant (lower, middle and upper canopy) were analyzedfor totalprotein by Auto Analyzer ZZMethod, totalphenol by Follin- Denis Method and total sugar content by L u h o o rMl ethod. The result showed that the older plant have the higher disease severity. The same trend can be seenjkm the age of leaves i.e. leaves fLom the lower part ofplants (olakr) am more susceptible than the middle and upper leaves. The critical period of the plant is at the age of 50 - 60 DAS. TotalJiuit production is not determined by disease severity, instead it is more determined by the age of plant infected. l%em is a tendency that the interaction among total protein and phenol content efect the susceptibility of the plant to the pathogen as can be seen the following regression equation: Y = 167 - 3.1 9 X2 - 22.58 X3 (R= 0.76).